Factors influencing risk-taking behaviour in Malaysia Islamic and conventional banks - Rafik, Harkati (IIUM Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2021)
The adoption of a dual banking system in Malaysia has ignited research on stability and instability brought about by the two different banking sectors in the financial system. Islamic banking is very short spanning a period of nearly five decade since its inception, and it is still developing its strategies and financial instruments based on Shariah principles to position itself in competitive stance in the face of the conventional counterpart that dates back more than four centuries earlier. The views are controversial in terms of which banking system is more risk-taking inclined, and whether Islamic banks risk-taking behaviour mimics that of conventional ones. While there are views supporting the distinction between Islamic banking system and its conventional counterpart owing to the former’s equity-based unique business contracts. Others maintain that conventional banking system is more efficient given its long historical record and the availability of various financial instruments. This thesis investigates the influence of assets, deposit and loans/financing concentration on risk-taking behaviour of Islamic and conventional banks, the influence of competition condition in the banking sector on risk-taking behaviour of Islamic and conventional banks, the influence of capital adequacy ratio stipulated in Basel III on risk-taking behaviour of Islamic and conventional banks, and the influence of economic freedom on risk-taking behaviour of Islamic and conventional banks. Employing General Least Square technique (GLS) on a panel data of 54 banks, 17 Islamic and 37 conventional, for the period 2011-2017, this study revealed that both concentration-instability and competition-instability views hold for both types of banks. Capital adequacy ratio fond to discourage risk-taking behaviour of both types of banks, while economic freedom found to encourage risk-taking of both types of banks. The size of influence for the four variables on risk-taking behaviour is higher for Islamic banks indicating that Islamic banks are more vulnerable than their conventional counterparts. The findings of the study also lend support to the notion that Islamic banks mimic conventional banks risk-taking behaviour. Therefore, both concentration-fragility and competition-fragility hypotheses can coexist. Moral hazard is not triggered in the Malaysian banking sector even though banks possess huge capital buffers implying successfulness of Basel III in controlling risk-taking behaviour of banks. Finally, Economic freedom should be considered as turns significant in determining risk behaviour of banks regardless of their type. Lastly, findings of the study have direct implications for banks, policymakers and decision makers in the banking industry, locally as well as globally. Islamic banks need further promotion to foster their market share (further penetration); this in turn will pave the way into a more competitive environment where banks can be more efficient and profitable in the face of increasing competition especially from their conventional counterparts. Since banks possess considerable capital buffers that serve as a supporting pillar, they are provided with enough flexibility to embark on wider business opportunities. The level of concentration and contestability in the Malaysian banking environment may need reconsideration to prepare Islamic banks for a future fierce competition. The number of Islamic banks in the industry needs further investigation. The level of economic freedom needs to be set at the best possible level that better serves banking stability and lessens banks inclination towards risk-taking.